The Effect of Remote Work Policy, Workplace Flexibility, and Employee Creativity in Enhancing Employee Productivity in State Owned Enterprises in Indonesia - Darojat, Ilma; Rosid, Muhammad Abdul; Isrok, Isrok; Fazira, Rabitha; Sudarmanto, Eko; Hasan, Muh (West Science Business and Management, 2025)
This study examines the effects of remote work policies, workplace flexibility, and employee creativity on employee productivity in state-owned enterprises (SOEs) in Indonesia. Employing a quantitative research design with 120 respondents, data were collected using a Likert-scale questionnaire (1-5) and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings reveal that remote work policies and workplace flexibility significantly enhance employee creativity and productivity. Moreover, employee creativity acts as a critical mediator, amplifying the effects of these organizational policies on productivity. The study underscores the importance of fostering a flexible and supportive work environment to enhance performance in SOEs, providing practical implications for policy formulation and leadership strategies.